Numerical analysis of NOX formation in CO2 diluted biogas premixed combustion - Sugeng Hadi Susilo (Scientific Route OÜ, 2021)
A further investigation of premixed biogas combustion towards the NOx formation is presented in this study. The purpose of the simulation is to determine the addition of CO2 in biogas fuel to the combustion behavior of premixed biogas on NOx formation, and to determine the occurrence of NOx in the pre-mixed biogas combustion. In this study, the Counterflow Premixed Flame class is used where this class is based on the One Dim class which is the basis for simulations with a 1-dimensional domain. The Counterflow Premixed Flame class uses an axisymmetric stagnation flow domain which has been written based on the equations. Cantera uses Newton's method to solve them. Completion is carried out in two stages. The first stage is to solve the solution using the equilibrium at each z coordinate point that has been determined. Many estimation starting points are determined from the start of the program. The second stage is the recalculation process at each point and then subdivided to get a smoother solution. The premixed excess CO2 biogas fuel and air combustion analyzed using a 1-dimensional numerical study. The diluted CO2 mass fraction ranged between 0–40 %. The CH4/CO2/air volume flow rate was maintained in ±L/min. The analysis implements the 1-D Counter Flow approach. Two counterflow nozzles were 20mm in diameter and the flame stagnation point at 10 mm. The results show that NOx mass fraction formed only on a fuel-lean mixture of CH4/CO2/air and its values decreased along with CO2 added. The addition of CO2 could reduce the NO species mass fraction down to 18 %, and NO2 reduction down to 7 %. This is mainly caused by a decreasing heat release rate of NO+N↔N2+O, N+O2↔NO+O, N+OH↔NO+H, and N+CO2↔NO+CO reactions. The N+CO2↔NO+CO reaction increased as CO2 was added but its values were not as much as the decline of three other reactions